Physical and Psychological Impact of the Phase One Lockdown for COVID-19 on Italians - Tommasi, Marco; Toro, Francesca; Arnò, Simone; Carrieri, Angelo; Conte, Marco Maria; Devastato, Marianna Daria; Picconi, Laura; Sergi, Maria Rita; Saggino, Aristide (Frontiers in Psychology, 2020)
The exceptional pandemic due to COVID-19 has obliged all Italians to stay at home. In literature there are evidences that traumatic global events, as natural catastrophes and pandemic, has negative effects on physical and psychological health of the population. We carried out a survey to analyze physical and psychological conditions of Italians during pandemic. Due to the severe limitations in moving during the phase one lockdown, the survey was administered by internet. Results show that Italians followed the provisions established by the Italian government to avoid contamination, but 43% of them declared to have suffered from physical symptoms, in particular migraine, sleep disorders, persistent exhaustion and difficulty of concentration. They have great fear to be contaminated or that relatives or friends can be contaminated and they actively take actions to avoid contamination. Participants declared they had suffered a lot of inconveniences due to restrictions in their movements and that their life habits were strongly changed. They spent their time at home in different activities but their psychological well-being was strongly impaired by the lockdown. The level of anxiety tripled, in relation to prepandemic period, and 30% of males and 41% of females declared to have severe levels of depression. Participants with high levels of optimism and hopefulness show a stronger resilience against anxiety and depression. In addition, there is a negative correlation between anxiety and depression and the five-factors of personality. These results show that psychological diseases must not to be neglected and that people in lockdown do need support for their psychological health, also with the help of internet and communication technologies.